The Relationship Between Stress Levels And Physical Activity With Premenstrual Syndrome In D3 Midwifery Stikes Griya Husada Sumbawa Students In 2022 - Ana Lestari; Rafi’ah Rafi’ah; Iga Maliga; Herni Hasifah; Nur Arifatus Sholihah (Sean Institute, 2023)
Pre-menstrual syndrome is thought to occur 7-14 days before menstruation and consists of physical, psychological and behavioral disturbances that can occur in women and can be triggered or exacerbated by factors such as their stress level and physical activity. This study aims to analyze the relationship between stress levels and physical activity and the occurrence of premenstrual syndrome in female students. This study used a quantitative analytical research method with a cross-sectional design. D3 Midwifery female students class of 2021-2024 were used as the sample (n = 32) in this study. Sampling was done by total sampling technique. The research instrument used the Depression Anxiety Stress Scale (DASS) questionnaire and the Shortened Premenstrual Assessment Form (SPAF). Data analysis used the Kendall tau test. The results of statistical tests showed that there was a relationship between stress levels and the incidence of premenstrual syndrome (0.001<0.05), with a correlation coefficient of 0.708 and there was a relationship between physical activity and the incidence of premenstrual syndrome (0.001<0.05) with a correlation coefficient of 0.066. It can be concluded that there is a significant relationship between stress levels and the incidence of premenstrual syndrome